2022
DOI: 10.1021/jacs.2c09120
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Oxidative Addition Mechanisms of Allylic Electrophiles with Low-Valent Ni/Co Catalysts Using Electroanalytical and Data Science Techniques

Abstract: The catalysis by a π-allyl-Co/Ni complex has drawn significant attention recently due to its distinct reactivity in reductive Co/Ni-catalyzed allylation reactions. Despite significant success in reaction development, the critical oxidative addition mechanism to form the π-allyl-Co/Ni complex remains unclear. Herein, we present a study to investigate this process with four catalysis-relevant complexes: Co(MeBPy)Br2, Co(MePhen)Br2, Ni(MeBPy)Br2, and Ni(MePhen)Br2. Enabled by an electroanalytical platform, Co(I)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 72 publications
2
39
0
Order By: Relevance
“…Our group and others have reported an electroanalytical approach to study oxidative addition processes involving low-valent first-row transition metals into alkyl electrophiles. The rate of oxidative addition is measured using cyclic voltammetry through peak-ratio analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our group and others have reported an electroanalytical approach to study oxidative addition processes involving low-valent first-row transition metals into alkyl electrophiles. The rate of oxidative addition is measured using cyclic voltammetry through peak-ratio analysis.…”
Section: Resultsmentioning
confidence: 99%
“…(See the Supporting Information for a more detailed discussion.) In prior studies, we have applied this method to study the oxidative addition processes of activated sp 3 electrophiles such as benzyl halides and allyl electrophiles . However, this method is yet to be applied to the reaction of aryl electrophiles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, several authors have suggested that the reaction follows a Co(II)−Co(I)−Co(III)−Co(II) cycle. 27,29,39,42 39 the reactive organometallic species that can react with aldehydes by a Zimmerman−Traxler transition state. 41 2 [E(2 •+ /2) = +1.31 V vs SCE (see Table 1)] was restored to the initial state by HE [E(HE •+ /HE) = +1.0 V vs SCE].…”
Section: ■ Results and Discussionmentioning
confidence: 99%